2008
DOI: 10.7903/cmr.1178
|View full text |Cite
|
Sign up to set email alerts
|

Asian Tourism Demand For Malaysia: A Bound Test Approach

Abstract: The objective of this paper is to investigate the long-run and short-run relationships among tourist arrivals to Malaysia and tourism price, substitute price, travelling cost, income and exchange rate for Asian7. The autoregressive distributed lag (ARDL) bounds test approach developed by Pesaran et al. (2001) is employed in the analysis, and the data cover the period 1970 to 2004. The empirical results show that in the long-run and short-run the tourism price, travelling cost, substitute price and income are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
6
21
0
1
Order By: Relevance
“…This is consistent with the theory of consumer behaviour and that of earlier studies (e.g. Kadir et al, 2008;Narayan, 2004;Salleh et al, 2008;Seetanah et al, 2010;Surugiu et al, 2011;Tan et al, 2002;Witt & Martin, 1987). The coefficient of lnP MAL,t reveals that by holding other factors constant, a 10% increase in the price of tourism in Malaysia would result in a 6.5% decline in per capita tourist arrivals from these 12 major tourism markets.…”
Section: Group Mean Fmols Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the theory of consumer behaviour and that of earlier studies (e.g. Kadir et al, 2008;Narayan, 2004;Salleh et al, 2008;Seetanah et al, 2010;Surugiu et al, 2011;Tan et al, 2002;Witt & Martin, 1987). The coefficient of lnP MAL,t reveals that by holding other factors constant, a 10% increase in the price of tourism in Malaysia would result in a 6.5% decline in per capita tourist arrivals from these 12 major tourism markets.…”
Section: Group Mean Fmols Resultssupporting
confidence: 90%
“…Some studies (e.g. Habibi et al, 2009;Hanafiah & Harun, 2010;Kadir et al, 2008;Kadir, Nayan, & Abdullah, 2013;Salleh et al, 2008Salleh et al, , 2007Tan, McCahon, & Miller, 2002) found that income has a significant positive impact on tourism demand in Malaysia. However, Kusni, Kadir, and Nayan (2013) and Ooi, Hooy, and Som (2013) discovered that income does not explain tourism demand in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies done by Mohd Salleh, Law, Ramachandran, Shuib, & Mohd Noor (2008), Ouerfelli (2008), Yang, Lin, & Han (2010), Ekanayake, Halkides, & Ledgerwood (2012) and Puah, Thien, & Arip (2014) have included exchange rate as independent variable and they consistently discovered that exchange rate is an important determinant for estimating tourism demand model. Exchange rate is proven to have a positive relationship with tourism demand in which appreciation or strengthening of tourist origin country's currency would improve tourists' spending power and resulted in more tourists are willing to travel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Malaysia's tourism literature can be classifi ed into three major groups: (i) a descriptive analysis of the tourism industry (for example, Wells, 1982;Wong, 1990;Smith, 1992;Cartier, 1998;Henderson, 2003;Syed Mustapa, 2005;Liu, 2006); (ii) the demand function for tourism (for example, Tan et al, 2003;Salleh et al, 2007Salleh et al, , 2008; and (iii) the dynamic of tourist arrivals and the impact of shocks (for example, Lean and Smyth, 2008;Lean and Smyth, 2009).…”
Section: Introductionmentioning
confidence: 99%